Local–Distortional Interaction in Cold-formed Steel Columns: Mechanics, Testing, Numerical Simulation and Design. (November 2015) - Martins, André Dias; Camotim, Dinar; Dinis, Pedro Borges; Young, Ben
Abstract: This paper provides an overview of the latest developments of the research activity carried out by the authors concerning the non-linear behaviour, ultimate strength and Direct Strength Method (DSM) design of cold-formed steel (plain and stiffened) columns experiencing local–distortional (L–D) interaction. Initially, numerical results obtained by means of Generalized Beam Theory (GBT) elastic post-buckling analyses are presented and their unique modal nature is used to illustrate and provide the main behavioural/mechanics features of this mode coupling phenomenon. Then, both experimental and numerical (obtained from Abaqus shell finite element analyses – SFEA) are presented and discussed, making it possible to provide clear evidence and characterize the column L-D interactive behaviour and failure. Besides reporting on two experimental test series performed by the authors, the paper also presents a critical review of other experimental results available in the literature concerning columns undergoing L–D interaction. The numerical results deal with columns exhibiting different cross-section shapes and fairly extensive parametric studies are carried out, in order to (i) assess the relevance of L–D interaction, as far as the ultimate strength erosion is concerned, and (ii) gather substantial ultimate strength data. Next, after showing the inadequacy of the currently codified DSM column design curves to predict L–D interactive failures, the paper presents and assesses the merits of DSM-based design approaches recently developed specifically to handle such failures.